2018
DOI: 10.1021/acs.accounts.7b00474
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Ethylene Carbonate–Propylene Carbonate Mystery in Li-Ion Batteries

Abstract: As one of the landmark technologies, Li-ion batteries (LIBs) have reshaped our life in the 21stcentury, but molecular-level understanding about the mechanism underneath this young chemistry is still insufficient. Despite their deceptively simple appearances with just three active components (cathode and anode separated by electrolyte), the actual processes in LIBs involve complexities at all length-scales, from Li migration within electrode lattices or across crystalline boundaries and interfaces to the Li acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
240
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 270 publications
(261 citation statements)
references
References 35 publications
7
240
0
2
Order By: Relevance
“…[8] Compared with EMC-solvated PF 6 À (4.5 V vs. Li/Li + ), EMC-solvated BF 4 -(4.7 V vs. Li/Li + ) appears more difficult to intercalate into graphite. Actually, ion-pair effect plays some role in the formation of SEI film at the graphite negative electrode in terms of lithium intercalation as well.…”
Section: Resultsmentioning
confidence: 97%
“…[8] Compared with EMC-solvated PF 6 À (4.5 V vs. Li/Li + ), EMC-solvated BF 4 -(4.7 V vs. Li/Li + ) appears more difficult to intercalate into graphite. Actually, ion-pair effect plays some role in the formation of SEI film at the graphite negative electrode in terms of lithium intercalation as well.…”
Section: Resultsmentioning
confidence: 97%
“…The energy gap between lowest unoccupied molecular orbital (LUMO) and highest occupied molecular orbital (HOMO) energy can predict the chemical stability of compounds . As the sole solvent, SL demonstrates the highest energy gap of 7.522 eV (Table S1, Supporting Information), indicating the highest chemical stability.…”
Section: Resultsmentioning
confidence: 99%
“…The energy gap between lowest unoccupied molecular orbital (LUMO) and highest occupied molecular orbital (HOMO) energy can predict the chemical stability of compounds. [79,80] As the sole solvent, SL demonstrates the highest energy gap of 7.522 eV (Table S1, Supporting Information), indicating the highest chemical stability. After 39 days storage at 80 °C, the unchanged -CH 2 -peaks (51.2 and 22.8 ppm in 13 C NMR spectra, Figure 7a; 3.04 and 2.23 ppm in 1 H NMR spectra, Figure 7b) confirm the excellent chemical stability of SL solvent.…”
Section: High Temperature Storage Of Electrolytementioning
confidence: 99%
“…PC, with the desired wide liquid temperature range but a relatively lower dielectric constant (64.92) than EC, is another attractive solvent for SIBs . PC is also compatible with hard carbon (HC), the predominant carbonaceous anode in SIBs, unlike its unappealing nature in LIBs, where the structural destruction of graphite anodes is caused by PC solvent cointercalation . Nevertheless, some studies also reported that the degradation of a SIB is strongly correlated with the continuous decomposition of PC .…”
Section: Carbonate Ester‐based Electrolytesmentioning
confidence: 99%